PENGARUH PERSONAL BRAND TITAN TYRA DI INSTAGRAM TERHADAP TINGKAT KEPERCAYAAN KONSUMEN PADA BRAND SECOND DATE BEAUTY - Allysa Eziira Ramdhani (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2025)
This research aims to analyze the influence of Titan Tyra's personal brand on Instagram on consumer trust in her beauty brand, Second Date Beauty. Influencers' personal brands play a vital role in fostering relationships between brands and audiences through social media platforms. Using a descriptive quantitative method, the study collected data from 200 respondents who follow Titan Tyra's Instagram account. This research explores key elements of personal branding, such as authenticity, trust, and emotional connection, which affect consumer perceptions of product quality and brand image. The findings show that Titan Tyra's digital presence significantly impacts consumer trust in Second Date Beauty, especially in terms of brand authenticity and personal engagement. These results highlight the importance of a strong and consistent personal brand in shaping consumer trust and loyalty in beauty products.